The national stem cell therapy patient registry of Malaysia — measuring clinical outcomes of stem cell therapy. - Loke, Seng Cheong (Humana Press, 2010)
Very few registries worldwide focus on clinical outcomes of stem cell therapy (SCT) as the large number of applications and rapid development of the field complicates registry design considerably. The National Stem Cell Therapy Patient Registry of Malaysia aims to accommodate this by using a main protocol which covers the overall design and administration of the registry, and condition-specific sub-protocols which deal with outcome measures. The registry will start with a few sub-protocols covering existing modes of SCT in Malaysia, with new sub-protocols released periodically as the need arises.